Bearing Steel Technology 2002
DOI: 10.1520/stp10870s
|View full text |Cite
|
Sign up to set email alerts
|

The Development of Bearing Steels with Long Life and High Corrosion Resistance

Abstract: The operating environments of rolling bearings are remarkably varied. With the use of bearings in various corrosive environments increasing, interest in stainless steel is growing. AISI 440C has been widely used in applications where corrosion resistance is of primary concern. However, its performance has not always been satisfactory because it contains coarse eutectic carbides that act as crack initiators under rolling contact stress and reduce Cr content in the martensitic matrix to the carbides. In response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…However, compared with AISI 52100, the dynamic load bearing capacity is lower and the steel contains coarse eutectic carbides (up to 60 μm) which can act as crack initiators and chromium concentration sites. 128,198 Martensitic stainless steel ES1 164,198 has a lower carbon and chromium content than AISI 440C to suppress eutectic carbides and has a comparable hardness to AISI 52100. M50 (through or case hardened) and M50NiL (case hardened) are secondary hardening steels with alloy carbides (Cr, Mo and V) more stable than cementite, are vacuum-induction remelted vacuum arc remelted (VIM-VAR) manufactured to reduced oxygen content and therefore non-metallic inclusions, and display a much reduced tendency to form WEA (butterflies) under normal operation loads.…”
Section: Tensile Hoop Stressmentioning
confidence: 99%
“…However, compared with AISI 52100, the dynamic load bearing capacity is lower and the steel contains coarse eutectic carbides (up to 60 μm) which can act as crack initiators and chromium concentration sites. 128,198 Martensitic stainless steel ES1 164,198 has a lower carbon and chromium content than AISI 440C to suppress eutectic carbides and has a comparable hardness to AISI 52100. M50 (through or case hardened) and M50NiL (case hardened) are secondary hardening steels with alloy carbides (Cr, Mo and V) more stable than cementite, are vacuum-induction remelted vacuum arc remelted (VIM-VAR) manufactured to reduced oxygen content and therefore non-metallic inclusions, and display a much reduced tendency to form WEA (butterflies) under normal operation loads.…”
Section: Tensile Hoop Stressmentioning
confidence: 99%
“…However, compared with AISI 52100, the dynamic load bearing capacity is lower and the steel contains coarse eutectic carbides which can act as crack initiators and chromium concentration sites. 80,84 Martensitic stainless steel ES1 51,84 has a lower carbon and chromium content than AISI 440C to suppress eutectic carbides and has a comparable hardness to AISI 52100. ES1 is alloyed with nitrogen which forms carbonitrides, strengthens the matrix and provides corrosion resistance, all the above enabling a tenfold increased WSF life compared with AISI 52100.…”
Section: Bearing Steelsmentioning
confidence: 99%
“…Also, many authors concluded that alloying stainless steel with N has a positive effect on general corrosion resistance. At the same time, it unambiguously improves the local corrosion resistance (stress corrosion cracking, pitting, intracrystalline corrosion, and crevice corrosion) [8][9][10][11][12]. According to the results obtained by Sakamut et al [13], increasing the content of N from 0.1 to 0.38 in austenitic stainless steel decreases corrosion rates in boiling 5% H2SO4 solution and in 10% HCl solution at a temperature of 25C.…”
Section: Introductionmentioning
confidence: 99%
“…Increasing of N from 0.06% to 0.18% in stainless steel grades -(20% Cr, 25% Ni), and (20% Cr, 25% Ni, 4.5% Mo) decreased the passive current density when tested in HCl and H2SO4 acids [16]. Speidel and others [8][9][10][11][12]17] interpreted the corrosion resistance of stainless-steel grades. They found that N dissolved in corrosion medium to form NH3, which increased pH and hence retarded the electrolyte at less acidic pit sites.…”
Section: Introductionmentioning
confidence: 99%